Coke segregation in the dry coke quenching unit - Kravchenko, Serhii; Miroshnichenko, Denis; Borisenko, Oleksandr (Національний технічний університет «Харківський політехнічний інститут», 2023)
The main reasons for the appearance of coke segregation when it is loaded into the chamber of a dry coke quenching unit (DCQU) are considered. The formation of the distribution of coke particles of different size along the height and cross-section of the quenching chamber begins already when the coke is unloaded into the DCQU prechamber and is determined by segregation processes. In the quenching chamber, zones with coke of different fractional composition and with different hydraulic resistance are formed, which, in the end, leads to different final temperatures of the quenched coke and, as a rule, to the need to increase the flow rate of the coolant. It is shown that the segregation of coke is already formed when it is discharged from the coking chamber into the coke carrier and then transferred to the DCQU prechamber. Methods for suppressing coke segregation occurring in a coke carrier when loading into a prechamber were tested on a scale model of the DCQU.

Розглянуто основні причини виникнення виділень коксу при його завантаженні в камеру установки сухого гасіння коксу (СУГК). Формування розподілу частинок коксу різного розміру по висоті та перерізу камери гасіння починається вже при вивантаженні коксу в форкамеру ДКВ і визначається процесами сегрегації. У камері гасіння утворюються зони з коксом різного фракційного складу і з різним гідравлічним опором, що в кінцевому результаті призводить до різної кінцевої температури гасіння коксу і, як правило, до необхідності збільшення витрати теплоносій. Показано, що сегрегація коксу вже утворюється, коли він вивантажується з камери коксування в коксоносій, а потім передається в передкамеру DCQU. Методи придушення сегрегації коксу, що відбувається в коксоносії при завантаженні у форкамеру, перевірені на масштабній моделі DCQU.
Виділення коксу в установці сухого гасіння коксу
Keywords: chamber; hopper; fractional composition; coke segregation; камера; бункер; фракційний склад; сегрегація коксу